2015
DOI: 10.1038/ncomms7604
|View full text |Cite
|
Sign up to set email alerts
|

Rise and fall of subclones from diagnosis to relapse in pediatric B-acute lymphoblastic leukaemia

Abstract: There is incomplete understanding of genetic heterogeneity and clonal evolution during cancer progression. Here we use deep whole-exome sequencing to describe the clonal architecture and evolution of 20 pediatric B-acute lymphoblastic leukaemias from diagnosis to relapse. We show that clonal diversity is comparable at diagnosis and relapse and clonal survival from diagnosis to relapse is not associated with mutation burden. Six pathways were frequently mutated, with NT5C2, CREBBP, WHSC1, TP53, USH2A, NRAS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
337
3
12

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 302 publications
(380 citation statements)
references
References 25 publications
25
337
3
12
Order By: Relevance
“…Relapse reflects two cooperating processes: the primary leukemogenic process driving the growth and survival of leukemic cells and the selection pressure imposed by frontline therapy. Similar to other studies of relapsed ALL (21,25,26,44,50,59), we observed increased RAS activation in relapse. Indeed, it has been proposed that RAS may mediate resistance to chemotherapy.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Relapse reflects two cooperating processes: the primary leukemogenic process driving the growth and survival of leukemic cells and the selection pressure imposed by frontline therapy. Similar to other studies of relapsed ALL (21,25,26,44,50,59), we observed increased RAS activation in relapse. Indeed, it has been proposed that RAS may mediate resistance to chemotherapy.…”
Section: Discussionsupporting
confidence: 80%
“…Intriguingly, however, we have found no NT5C2 mutations in our cohort. Previous studies identified NT5C2 mutations in 8-45% of the relapses of BCPALLs (34,35,44). Mutations in NT5C2 were associated with early relapses, whereas in our cohort the median time to relapse was relatively long, 1,071 d (range 375-2,226 d).…”
Section: Discussioncontrasting
confidence: 39%
See 2 more Smart Citations
“…Ma and colleagues confirmed the frequent mutation of NT5C2 in relapsed B-ALL and identified additional signaling pathways that are frequently mutated, including CREBBP, WHSC1, TP53, USH2A, NRAS and IKZF1. 8 While we have a comprehensive picture of the genomic complexity of T-ALL at diagnosis, 9-12 data on relapsed T-ALL cases are limited. In this issue of Haematologica, Kunz and colleagues explore the genetic basis and clonal evolution of diagnosis and relapse samples in pediatric T-ALL.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%